HEAVY METALS DISTRIBUTION TRENDS ON "OLESHKIVSKI PISKY" MILITARY TRAINING SITE - Splodytel, А. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The results of ecological-geochemical researches of soil cover of "Oleshkivski pisky" military training site, using maximum allowable concentration and classification of chemical elements with respect to hazard classes are presented. Analytical works to identify gross content and heavy metals movable forms in soils were defined by methods of atomic absorption and mass-spectometry with inductively coupled plasma (ICPMS) as well as by using gamma-ray activation analysis and X-ray fluorescence analysis. Analysis and interpretation of the coefficients of heavy metal components concentration were conducted based on landscape and geochemical fundamentals. The regular network of the protoselection points was developed. This network is built taking into account landscape structure of the territory, and provides control over landscape and geochemical currents and barriers. The average index of soil cover pollution of the polygon was calculated taking into account different toxicity of the elements. This index reaches its maximum in the region of firing positions and military polygon. The average Zc index of the upper soil level is 32, which corresponds to the dangerous level of soil pollution. The research revealed the content of moveable forms of heavy metals in soil cover of the polygon in order to identify toxic and tolerant levels of heavy metals concentration and reserve sources of elements in soils, which can maintain optimal concentration level in soil solution. It was defined that content of heavy metals in three movable forms are represented in the following geochemical units, mg/kg: in acid soluble form – Mn > Zn > Pb > Cu > V > Ni > Co > Cd; in exchangeable form – Mn > Zn > Pb > V > Co = Ni > Cu > Cd; in water soluble form – Mn > Zn > Pb = V > Co > Ni > Cd > Cu. The article presents research results on accumulation intensity and the nature of distribution of gross and mobile heavy metals forms in soil and on their migration in the soil profile. The dominant technogenic geochemical unit was extracted: Cd > Hg > Pb > Cu > Zn > Ni > V > Co > Mn. Landscapes with maximum polyelement contamination have been identified.
Keywords: heavy metals; speciation forms; summarized contamination rate; geochemical association; landscape; landscape-geochemical conditions